El Mercurio Peruano (1791-1795): historia y sociedad - Quiroz Chueca, Francisco (2014)
The periodical Mercurio Peruano (1791-1795) has been considered by conservative historians as a progressive and illustratedjournal, precursor of the Peruvian Independence. However, in recent times these claims are being challenged both from theperspective of philosophy and history. This study aims to establish the extent to which editors and external contributors to thejournal adhere to the illustrated principles in their study of national history and Peruvian society, and founds that the «mercuristas» follow rationalist elements in their historical analysis, but in terms of society they keep neoescolastic conceptions. Historicaltexts reject the providentialism of previous historiography, consider becoming as a civil and progressive historical path, try to beevidence-based but their approach is far from considering Andean past as a common history. On the other hand, «mercuristas»social analysis continues to be tied to old corporate and providential ideas.